Investigating the relationship between vitamin status and metabolic control in pediatric type 1 diabetes mellitus - Esam Yahya; Hamza M. Aldgini; Entsar A. Saad; Rabia O. Alghazeer; Rana R. El Sadda (Paediatrica Indonesiana, 2026)
Background Type 1 diabetes mellitus (T1DM) in children is characterized by persistent hyperglycemia, oxidative stress, and nutritional deficiencies that may worsen disease progression and complications. Fat-soluble vitamins and their binding proteins play key roles in antioxidant defense and immune modulation, yet their status in pediatric T1DM populations remains underexplored, particularly in North Africa. Objective To evaluate serum levels of vitamins A and D, along with their respective binding proteins: vitamin A-binding protein (VABP) and vitamin D-binding protein (VDBP), in Libyan children diagnosed with T1DM, and compare them with age- and sex-matched healthy controls. In addition, we aimed to investigate the relationship between vitamin A and D status, including their ratios to serum cholesterol, triglycerides, and glycemic control, as reflected by HbA1c levels. Methods In this case-control study, clinical and anthropometric data were collected from 90 Libyan children with T1DM and 90 age- and sex-matched healthy control group, including serum levels of vitamins A, D, and E, as well as the VABP and VDBP, which were measured using HPLC and ELISA. Lipid profiles were assessed, and vitamin-to-lipid ratios were calculated. Correlations with glycated hemoglobin (HbA1c) were evaluated using statistical modelling. Results Children with T1DM exhibited significantly higher mean HbA1c (9.2 (SD 1.1)% vs. 5.1 (SD 0.4)%, respectively; P<0.001), elevated triglycerides, and dyslipidemia compared with the control group. Mean serum concentrations of vitamin A [45.2 (SD 7.5) µg/dL], vitamin D [17.8 (SD 5.6) ng/mL], and vitamin E [11.2 (SD 1.3) mg/L], as well as VABP and VDBP, were significantly lower in the diabetic group (P<0.05 for all factors) compared to the non-diabetic control group. Lipid-adjusted vitamin ratios were consistently and significantly reduced, with the most pronounced deficits in vitamin A/cholesterol, vitamin D/triglyceride, and vitamin E/cholesterol (P<0.001). Significant inverse correlations were observed between HbA1c and both absolute vitamin levels and lipid-adjusted ratios. Conclusion Pediatric T1DM is associated with profound deficiencies in fat-soluble vitamins and their binding proteins, compounded by dyslipidemia that further reduces vitamin bioavailability. Lipid-adjusted vitamin ratios provide sensitive markers of metabolic imbalance and correlate with glycemic control. These findings support integrating nutritional assessment and targeted supplementation into routine T1DM management to improve metabolic regulation and mitigate long-term complications.